Preparation method of cellular microstructure nano functional film

By forming a polystyrene microsphere colloidal crystal template layer on the glass substrate and spreading the coating sol on the template layer for heat treatment, a honeycomb microstructure nanofunctional film was prepared, which solved the problem of complex and single functions of the existing microstructure film preparation method, and achieved multifunctionalization and efficient preparation of the film.

CN119912172AInactive Publication Date: 2025-05-02CNBM RESEARCH INSTITUTE FOR ADVANCED GLASS MATERIALS GROUP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510012726.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-05-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing microstructure film preparation methods are complex and have a single function, which cannot meet the multifunctional needs of glass functional films in terms of light, electricity, heat, etc.

Method used

The preparation method of honeycomb microstructure nanofunctional film is adopted, and a polystyrene microsphere colloidal crystal template layer is formed on the glass substrate by scraper coating technology, and then the coating sol is used to spread on the template layer and heat treatment is performed to remove the template to obtain the honeycomb microstructure nanofunctional film.

Benefits of technology

It is easy to prepare high-quality colloidal crystal templates on a large scale, and obtain a functional film with a honeycomb-like porous microstructure, which increases the reaction interface, improves the material utilization rate and reaction speed, and realizes the multifunctionalization of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912172A_ABST
    Figure CN119912172A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a cellular microstructure nano functional film, and belongs to the technical field of preparation of glass functional films. The invention provides a simple method for preparing a high-quality colloidal crystal template in a large area, the preparation method is simple, meanwhile, the layer number of the colloidal crystal template can be easily controlled, then, a functional film with a honeycomb porous microstructure surface is finally prepared, the honeycomb porous microstructure has a great specific surface area, and the specific surface area of the functional film is greatly increased. The reaction interface can be more effectively enlarged, the utilization rate of the material is improved, the reaction speed is increased, the characteristics of the film are enhanced, the application in different fields can be realized by using different coating sol, and the multi-functionalization of the film is realized. The prepared film has important application value in the technical field of preparation of glass functional films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass functional film preparation, and in particular, relates to a method for preparing a honeycomb microstructure nano functional film. Background Art

[0002] The regulation of material microstructure is a new type of high-performance material realization and acquisition method that has emerged and received widespread attention in the field of nanomaterials in recent years. It imitates various interesting and exquisite biological natural structures or biological structures in nature. These structures often have certain special properties required for our social applications, such as: the high regularity of honeycomb structure, the super hydrophobicity of lotus leaf surface, the desiccation resistance of cactus, etc. These extraordinary properties are determined by their surface microstructures, and these excellent properties are also what we hope to apply in artificial materials.

[0003] In the field of glass, the construction of microstructured films is an important way to improve the functionality (optical, electrical, thermal, etc.) of glass films. Compared with flat films, the microstructuring of the film surface will inevitably increase its specific surface area, which increases the contact surface between the film and the phase medium. For the most important optical properties of glass, when light passes through the microstructure, scattering will occur, causing the incident angle to shift, resulting in an anti-reflection effect; at the same time, the construction of microstructures on the glass surface has an extremely important influence on the wettability of the glass surface. Such means can be used to achieve super-hydrophilic or super-hydrophobic glass surfaces, which are advantages that flat dielectric films do not have. In addition, for certain specific dielectric films such as TiO2, SiO2, WO3 films, etc., the construction of surface microstructures can greatly improve their photocatalytic properties, anti-transmittance, electrochromic properties, etc. However, the current preparation methods of microstructured films are relatively complicated, and the functions are single, which cannot meet people's needs well. Therefore, it is urgent to invent a microstructured nanofilm with a simple preparation method and diverse functions to meet the higher demands in the field of glass functional film preparation technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing a honeycomb microstructure nano-functional film.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a honeycomb microstructure nano-functional film comprises the following steps:

[0007] A1. Use a flat glass substrate and place it on the coating plane of a doctor blade coating machine. Place a doctor blade coating rod at the top edge of the glass substrate. Add polystyrene microsphere ethanol emulsion dropwise onto the doctor blade coating rod. The emulsion flows to the contact line between the rod and the substrate under the action of gravity. Under the action of surface tension, the emulsion is evenly adsorbed on the contact line between the rod and the substrate.

[0008] A2. Turn on the wire rod coating switch of the coating machine, and let the wire rod move downward on the surface of the glass substrate at a uniform speed until it reaches the lower edge of the glass substrate; let it stand until the ethanol is completely evaporated, and a colloidal crystal template layer composed of polystyrene microspheres is formed on the surface of the substrate;

[0009] A3, use a coating wire rod of the same specification as step A1, place it on the upper edge of the glass coated with the template layer obtained in step A2, drip the coating sol on the wire rod, and evenly spread the coating sol on the contact line between the wire rod and the substrate. Turn on the coating switch, and the wire rod moves downward at a uniform speed on the surface of the glass coated with the template until it reaches the lower edge of the glass. At this time, the coating sol is evenly spread on the entire glass surface until the liquid sol penetrates into the template gap under the action of gravity;

[0010] A4. After the glass coated with the coating sol obtained in step A3 is allowed to stand, it is dried to obtain coated glass. The coated glass is heat-treated to remove the polystyrene template by thermal cracking to obtain a honeycomb microstructure nano-functional film.

[0011] Furthermore, the specification of the coating wire rod in step A1 is 2-20 μm.

[0012] Furthermore, the solid content concentration of the polystyrene microsphere ethanol emulsion in step A1 is 2-10%.

[0013] Furthermore, in step A2, the speed of the wire rod is 1-5 m / min.

[0014] Furthermore, in step A3, the speed of the wire rod is 1-5 m / min.

[0015] Furthermore, the standing condition in step A4 is standing at room temperature for 0.1-1h.

[0016] Furthermore, in step A4, the drying condition is 80-120° C. for 1-2 h.

[0017] Furthermore, in step A4, the heat treatment conditions are 350-600° C. and the time is 1-3 h.

[0018] Furthermore, the coating sol is one of electrochromic WO3 sol, ionic electrolyte LiTaO3, AlPO4 sol, photocatalytic TiO2 sol and optically anti-reflective SiO2 sol.

[0019] Beneficial effects of the present invention:

[0020] The present invention firstly provides a simple method for preparing high-quality colloidal crystal templates over a large area. Not only is the preparation method simple, but the number of colloidal crystal template layers can also be easily controlled. Secondly, a functional film having a honeycomb porous microstructure surface is finally obtained. The honeycomb porous microstructure has a very large specific surface area, which can more effectively increase the reaction interface, improve the utilization rate of materials and increase the reaction rate, thereby enhancing the properties of the film. In addition, by using different coating sols, the film can be applied in different fields, thereby realizing the multifunctionality of the film. In summary, the film prepared by the present invention has important application value in the field of glass functional film preparation technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The present invention will be further described below in conjunction with the accompanying drawings.

[0022] Figure 1 This is an optical profilometer scanning picture of the surface morphology of a typical polystyrene microsphere colloidal crystal template prepared on a glass substrate in Example 1 of the present invention.

[0023] Figure 2 This is a scanned image of the surface morphology of the honeycomb porous microstructure functional film prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Embodiment 1

[0026] A1. Use a flat glass as a substrate and place it on the coating plane of a doctor blade coating machine. Place a 2μm doctor blade coating wire rod at the uppermost edge of the glass substrate. Add polystyrene microsphere ethanol emulsion (solid content of 2%) dropwise onto the doctor blade coating wire rod. The emulsion flows to the contact line between the wire rod and the substrate under the action of gravity. Under the action of surface tension, the emulsion is evenly adsorbed on the contact line between the wire rod and the substrate.

[0027] A2. Turn on the wire rod coating switch of the coating machine, and the wire rod moves downward on the surface of the glass substrate at a uniform speed of 1m / min until it reaches the lower edge of the glass substrate; let it stand until the ethanol is completely evaporated, and a colloidal crystal template layer composed of polystyrene microspheres is formed on the substrate surface; the structure is as shown in FIG. Figure 1 As shown;

[0028] A3, use a 2μm coating wire rod, place it on the upper edge of the glass coated with the template layer obtained in step A2, drip the coating sol on the wire rod, and evenly spread the coating sol on the contact line between the wire rod and the substrate. Turn on the coating switch, and the wire rod moves downward on the surface of the glass coated with the template at a uniform speed of 1m / min until it reaches the lower edge of the glass. At this time, the coating sol is evenly spread on the entire glass surface until the liquid phase sol penetrates into the template gap under the action of gravity;

[0029] A4, the glass coated with the coating sol obtained in step A3 was allowed to stand at room temperature for 0.1h, and dried at 80°C for 1h to obtain coated glass, and the coated glass was heat treated at 350°C for 1h to remove the polystyrene template by thermal decomposition to obtain a honeycomb microstructure nano-functional film; the surface morphology scanning diagram is as follows Figure 2 As shown;

[0030] The coating sol is WO3 coating sol, which is prepared by the following steps:

[0031] Add 100mL of H2O2 into the flask, slowly pour 5g of tungsten powder into the H2O2, and quickly move the flask into a 5°C ice water bath, stirring continuously to allow the tungsten powder and hydrogen peroxide to fully react for 2 hours, then filter, wash the filter residue with water, and dry it in an oven at 80°C to obtain a WO3 coating sol.

[0032] Embodiment 2

[0033] A1. Use a flat glass as a substrate and place it on the coating plane of a doctor blade coating machine. Place a 20μm doctor blade coating wire rod at the uppermost edge of the glass substrate. Add polystyrene microsphere ethanol emulsion (solid content of 10%) dropwise onto the doctor blade coating wire rod. The emulsion flows to the contact line between the wire rod and the substrate under the action of gravity. Under the action of surface tension, the emulsion is evenly adsorbed on the contact line between the wire rod and the substrate.

[0034] A2. Turn on the wire rod coating switch of the coating machine, and move the wire rod downward on the surface of the glass substrate at a uniform speed of 5 m / min until it reaches the lower edge of the glass substrate; let it stand until the ethanol is completely evaporated, and a colloidal crystal template layer composed of polystyrene microspheres is formed on the surface of the substrate;

[0035] A3, use a 20 μm coating wire rod, place it on the upper edge of the glass coated with the template layer obtained in step A2, drip the coating sol on the wire rod, and evenly spread the coating sol on the contact line between the wire rod and the substrate. Turn on the coating switch, and the wire rod moves downward on the surface of the glass coated with the template at a uniform speed of 5 m / min until it reaches the lower edge of the glass. At this time, the coating sol is evenly spread on the entire glass surface until the liquid sol penetrates into the template gap under the action of gravity;

[0036] A4, the glass coated with the coating sol obtained in step A3 is allowed to stand at room temperature for 1 hour, and dried at 120°C for 2 hours to obtain coated glass, and the coated glass is heat-treated at 600°C for 3 hours to thermally decompose and remove the polystyrene template to obtain a honeycomb microstructure nano-functional film;

[0037] Wherein, the coating sol is TiO2 coating sol, which is prepared by the following steps:

[0038] Mix 10 mL of butyl phthalate and 100 mL of anhydrous ethanol evenly, add 4.5 mL of acetylacetone, let stand for 2 hours, then drop 50 mL of deionized water to hydrolyze the butyl phthalate, add acetic acid solution (mass fraction 12%) to adjust the solution pH to 3.0, finally add N,N-dimethylformamide, stir for 3 hours and let stand for 24 hours to obtain a TiO2 coating sol.

[0039] Comparative Example 1

[0040] Tungsten oxide electrochromic thin film produced by magnetron sputtering.

[0041] Comparative Example 2

[0042] A commercially available titanium dioxide film was used.

[0043] The electrochromic performance of Example 1 and Comparative Example 1 was measured by the following test method:

[0044] An electrochemical workstation and a UV-visible spectrophotometer were used to measure the light transmittance change and electrochromic response speed of the samples, and the coloring efficiency was calculated.

[0045] The measured results are shown in Table 1:

[0046] Table 1

[0047] Test items Embodiment 1 Comparative Example 1 <![CDATA[Coloring efficiency / (cm 2 / C)]]> 47.6 39.1

[0048] The photocatalytic activity of Example 2 and Comparative Example 2 was tested by the following method:

[0049] 25 mL of a methylene blue dye solution with a mass concentration of 50 mg / L was measured and placed in a photocatalytic reactor, and the sample was placed flat in the reactor; a 500 W xenon lamp was used as a light source, and a JZ-420 filter was used to filter out light below 420 nm for a photocatalytic degradation experiment, and the absorbance of the solution was measured at the maximum absorption wavelength using a visible spectrophotometer, thereby calculating the residual dye concentration in the solution after illumination, and calculating the degradation rate; degradation rate / %=(concentration of the dye solution before photodegradation-concentration of the dye solution after photodegradation) / concentration of the dye solution before photodegradation×100%.

[0050] The measured results are shown in Table 2:

[0051] Table 2

[0052] Test items Embodiment 2 Comparative Example 2 Degradation rate / % 98.7 88.4

[0053] It can be seen from the above two tables that the film prepared by the present invention contains a honeycomb porous microstructure, so that it can achieve higher performance when combined with coating sols with different functions. Therefore, the film prepared by the present invention has important application value in the field of glass functional film preparation technology.

[0054] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0055] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a honeycomb microstructure nano-functional film, characterized in that: The following steps are involved: A1. Use a flat glass substrate and place it on the coating plane of a doctor blade coating machine. Place a doctor blade coating rod at the top edge of the glass substrate. Add polystyrene microsphere ethanol emulsion dropwise onto the doctor blade coating rod. The emulsion flows to the contact line between the rod and the substrate under the action of gravity. Under the action of surface tension, the emulsion is evenly adsorbed on the contact line between the rod and the substrate. A2. Turn on the wire rod coating switch of the coating machine, and let the wire rod move downward on the surface of the glass substrate at a uniform speed until it reaches the lower edge of the glass substrate; let it stand until the ethanol is completely evaporated, and a colloidal crystal template layer composed of polystyrene microspheres is formed on the surface of the substrate; A3, use a coating wire rod of the same specification as step A1, place it on the upper edge of the glass coated with the template layer obtained in step A2, drip the coating sol on the wire rod, and evenly spread the coating sol on the contact line between the wire rod and the substrate. Turn on the coating switch, and the wire rod moves downward at a uniform speed on the surface of the glass coated with the template until it reaches the lower edge of the glass. At this time, the coating sol is evenly spread on the entire glass surface until the liquid sol penetrates into the template gap under the action of gravity; A4. After the glass coated with the coating sol obtained in step A3 is allowed to stand, it is dried to obtain coated glass. The coated glass is heat-treated to obtain a honeycomb microstructure nano-functional film.

2. The method for preparing a honeycomb microstructure nano-functional film according to claim 1, characterized in that: The specification of the coating wire rod in step A1 is 2-20 μm.

3. The method for preparing a honeycomb microstructure nano-functional film according to claim 1, characterized in that: The solid content of the polystyrene microsphere ethanol emulsion in step A1 is 2-10%.

4. The method for preparing a honeycomb microstructure nano-functional film according to claim 1, characterized in that: The speed of the wire rod in step A2 is 1-5 m / min.

5. The method for preparing a honeycomb microstructure nano-functional film according to claim 1, characterized in that: The standing condition in step A4 is standing at room temperature for 0.1-1 h.

6. The method for preparing a honeycomb microstructure nano-functional film according to claim 1, characterized in that: The drying condition in step A4 is drying at 80-120° C. for 1-2 h.

7. The method for preparing a honeycomb microstructure nano-functional film according to claim 1, characterized in that: The heat treatment conditions in step A4 are 350-600° C. and the time is 1-3 h.

8. The method for preparing a honeycomb microstructure nano-functional film according to claim 1, characterized in that: The coating sol is one of electrochromic WO3 sol, ionic electrolyte LiTaO3, AlPO4 sol, photocatalytic TiO2 sol and optically anti-reflective SiO2 sol.

Citation Information

Patent Citations

  • Preparation method of porous super-hydrophilic film with photocatalytic performance

    CN106630666A

  • Preparation method of large-area layer number-controllable colloidal crystal

    CN109553788A